2011
DOI: 10.1186/1471-2334-11-340
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of cryptococcosis of the bilateral adrenal glands and liver by unilateral adrenalectomy with antifungal agents: a case report

Abstract: BackgroundCryptococcus species usually affect the central nervous system and lungs in immunocompromised hosts. Although the adrenal glands can be involved in disseminated cryptococcosis, primary adrenal insufficiency caused by the fungal infection is uncommon.Case presentationWe present a case of primary adrenal insufficiency with bilateral adrenal masses and liver invasion in a 43-year-old man with mild type 2 diabetes mellitus. Cryptococcosis was diagnosed by fine-needle aspiration biopsy of the liver mass. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Matsuda et al reported that, despite the presence of bilateral adrenal masses in their patient, they chose to perform unilateral adrenalectomy because adhesion of the right adrenal mass to the liver was anticipated, which may have caused massive bleeding. Unilateral adrenalectomy led to remarkable decreases in the serum cryptococcal antigen titers and a reduction in the size of the remaining right adrenal mass ( 11 ). If the masses in the adrenal gland or liver start to become enlarged or the Cryptococcus antigen titer is elevated, unilateral adrenalectomy should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuda et al reported that, despite the presence of bilateral adrenal masses in their patient, they chose to perform unilateral adrenalectomy because adhesion of the right adrenal mass to the liver was anticipated, which may have caused massive bleeding. Unilateral adrenalectomy led to remarkable decreases in the serum cryptococcal antigen titers and a reduction in the size of the remaining right adrenal mass ( 11 ). If the masses in the adrenal gland or liver start to become enlarged or the Cryptococcus antigen titer is elevated, unilateral adrenalectomy should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the reports, the enlargement was mentioned [58] at the diagnosis or did not change, even after the antifungal treatment was effective [914]. There is only one report which shows a decrease in adrenal gland enlargement after treatment with amphotericin B [15]; however, the images obtained after treatment clearly showed adrenal gland enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…The infected glands showed caseating necrosis [5, 6, 10, 13, 16] or necrotizing granuloma [6, 14], accompanied by yeast-like organism, chronic inflammation with giant cells, multinucleated histiocytes, and a few lymphocytes. Although there were no histological data from the adrenal glands in this patient, infiltration of inflammatory cells into the adrenal glands could cause the enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…The patient presented with diabetes mellitus and roentgenographic findings were suggestive of a malignant tumor . Matsuda et al described a case of adrenal cryptococcosis in a patient who also presented with adrenal insufficiency . FNA cytology established the diagnosis of cryptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…Cell block sections from positive FNA cases when stained with mucicarmine show a characteristic pink staining of the capsule. Radiologic imaging and FNA of the adrenal gland is often helpful in the diagnosis of adrenal gland mass lesions . Bilateral adrenal enlargement can be caused by metastatic disease, hyperplasia, or infection and a definitive diagnosis can be readily provided using FNA …”
mentioning
confidence: 99%